2017
DOI: 10.1111/bcpt.12842
|View full text |Cite
|
Sign up to set email alerts
|

GSTP1 c.313A>G, XPD c.934G>A, XPF c.2505T>C and CASP9 c.‐1339A>G Polymorphisms and Severity of Vomiting in Head and Neck Cancer Patients treated with Cisplatin Chemoradiation

Abstract: Cisplatin (CDDP) chemotherapy associated with radiation (RT) has been used in advanced head and neck squamous cell carcinoma (HNSCC) patients, and vomiting is a common side effect during treatment. This prospective study aimed to identify the roles of GSTM1 and GSTT1 (presents or nulls), GSTP1 c.313A>G, XPC c.2815A>C, XPD c.934G>A and c.2251A>C, XPF c.2505T>C, ERCC1 c.354C>T, MLH1 c.-93G>A, MSH2 c.211 + 9C>G, MSH3 c.3133G>A, EXO1 c.1765G>A, TP53 c.215G>C, CASP3 c.-1191A>G and c.-1168G>T, CASP9 c.-1339A>G, CASP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…31 DNA damage is associated with an increased risk of cancer, in which the reduced capacity of DNA repair can accelerate changes and mutations in essential genes, triggering carcinogenesis. 13,20,29 In this study, we observed a significant difference in the cytoplasmic protein expression of XPF between the OTSCC and LLSCC groups, with higher expression in OTSCC cases; however, there was no association with the clinical parameters analyzed. This cytoplasmic expression of XPF may indicate deregulation of protein function in OTSCC, which could contribute to the more aggressive behavior of the tumor at this anatomical site.…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…31 DNA damage is associated with an increased risk of cancer, in which the reduced capacity of DNA repair can accelerate changes and mutations in essential genes, triggering carcinogenesis. 13,20,29 In this study, we observed a significant difference in the cytoplasmic protein expression of XPF between the OTSCC and LLSCC groups, with higher expression in OTSCC cases; however, there was no association with the clinical parameters analyzed. This cytoplasmic expression of XPF may indicate deregulation of protein function in OTSCC, which could contribute to the more aggressive behavior of the tumor at this anatomical site.…”
Section: Discussionmentioning
confidence: 44%
“…Studies using cells from XPF-deficient patients and animal models have shown that low expression of XPF is associated with higher sensitivity to DNA-damaging agents. 21,29 Ang et al 21 observed high nuclear expression of protein XRCC1 in head and neck carcinomas, which was related to poor patient survival, especially among those undergoing chemotherapy. In the study of Mahjabeen et al, 14 expression of XRCC1 was associated with poor survival in a series of head and neck carcinomas and immunostaining for the protein was observed in both cytoplasm and nucleus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the observed data consist of a prospective non-interventional study performed in the same institution, where 88 patients were submitted to high-dose CDDP and radiotherapy without the use of fosaprepitant. [14] For the prior risk of the GSTP1 c.313 AG or GG genotype, we considered an additional prospective case-control study from a similar sample population of 229 patients. [28] The probability of grade 3 or 4 CINV was collected from a current meta-analysis (three-weekly CDDP arm), [29] while the chance of chemotherapy dropouts and suspensions was obtained from the intervention arm (N = 179) of a randomized clinical trial assessing high-dose CDDP and radiotherapy.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, patients with head and neck cancer (HNC) under chemoradiation therapy with high-dose CDDP were prospectively evaluated in our institution, aiming to identify a possible correlation between single nucleotide polymorphisms (SNPs) involved in CDDP metabolism and the occurrence of CINV. [14] In this setting, the prophylaxis consisted of dexamethasone in combination with the 5-HT3 antagonist ondansetron, which is supported by the public health system in Brazil. Among the SNPs studied, the glutathione S-transferase P gene ( GSTP1 ) c.313 (NM_000852.3, rs1695) was highlighted.…”
Section: Introductionmentioning
confidence: 99%